The relationship of effective communication and safety culture in construction industry in Malaysia - Ahmad Faisal Mohamed Fiah; Norhuda Salleh; Romlah Ramli; Noor Syakirah Zakaria (Global Academic Excellence (M) Sdn Bhd, 2022)
This paper discusses on the relationship of effective communication and safety culture in construction industry. Generally, lack of communication at workplace and for this case, construction and project site is part of contributing factor in accident and some of the accidents involved fatalities. In any areas especially those involving human, communication is a key factor towards producing an optimum result. Lack of communication and understanding of safety culture if is not done effectively can lead to error and defect especially in construction industry since construction industry not only dealing with human but also other aspects such big machines and those machines operated by human. Safety culture among construction workers and project owners is also another crucial element in construction industry but safety culture can only be achieved if the message is communicated effectively. Therefore, this paper discusses on the relationship and importance of effective communication and safety culture and generally how it is implemented in construction industry in Malaysia.